GZ7 and GZ8 – Two Zircon Reference Materials for SIMS U‐Pb Geochronology. Issue 4 (8th October 2018) - Nasdala, Lutz; Corfu, Fernando; Schoene, Blair; Tapster, Simon R.; Wall, Corey J.; Schmitz, Mark D.; Ovtcharova, Maria; Schaltegger, Urs; Kennedy, Allen K.; Kronz, Andreas; Reiners, Peter W.; Yang, Yue‐Heng; et al.
Abstract : Here, we document a detailed characterisation of two zircon gemstones, GZ7 and GZ8. Both stones had the same mass at 19.2 carats (3.84 g) each; both came from placer deposits in the Ratnapura district, Sri Lanka. The U‐Pb data are in both cases concordant within the uncertainties of decay constants and yield weighted mean 206 Pb/ 238 U ages (95% confidence uncertainty) of 530.26 Ma ± 0.05 Ma (GZ7) and 543.92 Ma ± 0.06 Ma (GZ8). Neither GZ7 nor GZ8 have been subjected to any gem enhancement by heating. Structure‐related parameters correspond well with the calculated alpha doses of 1.48 × 10 18  g −1 (GZ7) and 2.53 × 10 18  g −1 (GZ8), respectively, and the (U‐Th)/He ages of 438 Ma ± 3 Ma (2 s ) for GZ7 and 426 Ma ± 9 Ma (2 s ) for GZ8 are typical of unheated zircon from Sri Lanka. The mean U mass fractions are 680 μg g −1 (GZ7) and 1305 μg g −1 (GZ8). The two zircon samples are proposed as reference materials for SIMS (secondary ion mass spectrometry) U‐Pb geochronology. In addition, GZ7 (Ti mass fractions 25.08 μg g −1  ± 0.18 μg g −1 ; 95% confidence uncertainty) may prove useful as reference material for Ti‐in‐zircon temperature estimates. Key Points: We document a detailed characterisation of the Sri Lankan zircon gemstones GZ7 and GZ8 and propose them as SIMS U‐Pb reference materials. Both specimens have high mean U mass fractions and concordant Cambrian (GZ7) and Ediacaran (GZ8) U‐Pb ages. In addition, GZ7 is proposed as a reference material for Ti‐in‐zircon temperature estimates.